The effects of firing costs on employment and hours per employee - Yannic Stucki; Jacqueline Thomet (University of Bern, Department of Economics, 2018)
We explore the role of firing costs on labor market outcomes in a search and matching framework with distinct decisions on the intensive (hours per employee) and extensive (employment) margins of labor supply. We show that allowing for two distinct labor supply margins matters for assessing firing costs. When the intensive margin is kept fixed (as is typically done in empirical work on firing costs), the dampening effect of firing costs on employment fluctuations is strongly understated. Further, in a quantitative exercise, we calibrate firing costs to represent the different employment protection regulations across OECD countries. We find that with firing costs of a similar size as in France, the drop in US employment during the Great Recession would have been a third its size.
Keywords: E32; F44; J22; 330; Search and matching; firing costs; employment protection legislation; labor supply margins